2004
DOI: 10.1002/jnr.20354
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the neuronal marker NeuN as a multiply phosphorylated antigen with discrete subcellular localization

Abstract: NeuN (neuronal nuclei) is an antigen used widely in research and diagnostics to identify postmitotic neurons. The present study aims at an initial understanding of the molecular nature and functional significance of this as yet ill-defined antigen. Using isoelectric focusing, both the 46- and 48-kDa isoforms of NeuN can be separated in multiple spots spanning a pH range of 8-10.5, suggesting that they might be phosphorylated. Enzymatic dephosphorylation abolishes NeuN immunoreactivity, confirming that NeuN is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
161
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 22 publications
18
161
0
1
Order By: Relevance
“…NPY expression patterns were analyzed in conjunction with cellular markers that provided a clear demarcation of acute neuronal injury and neurodegeneration in and proximal to the infarct core as well as potential effects remote from the lesion. Although Nissl staining suggested that the hippocampus was spared direct injury by cortical photothrombosis and FJB-positive somata were not detected in the hippocampus at any time following photothrombosis, reduced NeuN IR in the hippocampus suggested some degree of neuronal dysfunction and/or a changed phosphorylation state of the NeuN protein (Lind et al, 2005). The distribution of increased GFAP IR was similar to that previously reported for the photothrombosis model (Bidmon et al, 2001b;Kharlamov et al, 2000;Oermann et al, 2004;Schroeter et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…NPY expression patterns were analyzed in conjunction with cellular markers that provided a clear demarcation of acute neuronal injury and neurodegeneration in and proximal to the infarct core as well as potential effects remote from the lesion. Although Nissl staining suggested that the hippocampus was spared direct injury by cortical photothrombosis and FJB-positive somata were not detected in the hippocampus at any time following photothrombosis, reduced NeuN IR in the hippocampus suggested some degree of neuronal dysfunction and/or a changed phosphorylation state of the NeuN protein (Lind et al, 2005). The distribution of increased GFAP IR was similar to that previously reported for the photothrombosis model (Bidmon et al, 2001b;Kharlamov et al, 2000;Oermann et al, 2004;Schroeter et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…Large granule cells contain scarce heterochromatin and stain more intensely for NeuN, whereas the evenly distributed fine heterochromatin granules in small granule cells stain less intensely for NeuN. This is in accordance with the observation that NeuN is expressed preferentially in areas of low chromatin density (Lind et al, 2005), indicating a higher cell activity in large granule cells. Thus, large granule cells may be also functionally related to adult born granule cells, as these cells have been shown to be more excitable than the resident granule cells (Schmidt-Hieber et al, 2004;Wang et al, 2000).…”
Section: Resident Granule Cells and Their Relation To Neurogenesissupporting
confidence: 89%
“…Similar cellular expression profiles have been described in mouse and chicken, including a common lack of label in Purkinje cells of the cerebellum (Mezey et al 2012;Weyer and Schilling 2003). Specificity has been verified with Western blots using chicken protein extracted from whole brains which showed specific bands at estimated molecular weights of 46 and 48 kDa (Mezey et al 2012), similar to mouse (Lind et al 2005). NeuN has been used extensively to label postmitotic neurons in developmental studies in chick (Mezey et al 2012;Perez et al 1999;Zeng et al 2008) and in a study of cochlear nucleus neurons in mice (Mostafapour et al 2002).…”
Section: Neun Antibody Specificitysupporting
confidence: 62%